(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article discusses the development of the labor markets of the Ukrainian-Polish borderland position s European integration prospects. Specified in geospatial and socio-economic approaches to study it. The features of the labor market research at the local level. The results of the comparative analysis of the costs and benefits of individual local border RRP Lviv region covered General analysis of the experience of transformation of thрe Polish economy presented (H. Holaya in estimates).Develop proposals on their account in the strategy of sustainable development of the border region.